Genetic Potential and Inheritance Pattern of Phenological Growth and Drought Tolerance in Cotton (Gossypium Hirsutum L.) - Mahmood, Tahir; Wang, Xiukang; Ahmar, Sunny; Abdullah, Muhammad; Iqbal, Muhammad Shahid; Rana, Rashid Mehmood; Yasir, Muhammad; Khalid, Shiguftah; Javed, Talha; Mora-Poblete, Freddy; Chen, Jen-Tsung; Shah, Muhammad Kausar Nawaz; et al. (Frontiers in Plant Science, 2021)
Cotton has prime importance in the global economy and governs socio-economic affairs of the world. Water scarcity and high temperature are major constraints that badly affect cotton production, which shows the need for the development of drought-tolerant varieties. Ten cotton genotypes, including three drought-tolerant and seven susceptible, were identified from a panel of diverse cotton genotypes at the seedling stage under two contrasting water regimes. Three lines were crossed with seven testers under line × tester mating design. The 21 F1 cross combinations along with 10 parents were evaluated under 100% non-stress (NS) and 50% drought stress (DS) filed capacity to assess the effects of drought stress and its inheritance in the next generation. All the genotypes were evaluated till the maturity stage for combining ability, heritability, and other genetic factors to understand the drought tolerance mechanisms. The proportional contribution of lines in the total variance evidenced that lines had a significant higher contribution in total variance for days to boll opening (DBO) of 10% and proline contents (PC) of 13% under DS conditions. It indicates that lines contributed more positive alleles for such traits. Under DS condition, DTV-9 × BT-252 and DTV-9 × DTV-10 had maximum negative specific combining ability (SCA) effects for DBO. Simultaneously, DBO also had higher heritability (h2) which indicates its dominant gene action and meanwhile, the importance of these combinations for the early mature and short duration variety development. The results revealed that most of the studied traits, including days taken to maturity, yield traits, and physiological traits, are under significant genetic control, with a strong genetic basis and have a huge potential for improving drought tolerance in cotton. Drought tolerance was found to have a strong association with early maturity and agro-climatic conditions of the cultivated areas. Identified superior parents in this study are suggested to use in the future breeding program to advance the cotton growth and drought tolerance.